Density and housing: Comparative evaluation towards a Residential Quality Index. The case of Collective Dwellings in Córdoba, Argentina - Marengo, Maria Cecilia (2017)
The crisis on infrastructure systems, mobility and the demands of service provision in increasingly remote areas with less values of urbanity that resultfrom the dispersed city model, leads to reexamining the consolidated anddense tissues. While presenting a more compact land-use, there should beconditions of urban habitability of higher quality than those in the new undifferentiated and diffuse peripheries. In this context, the research analyzescomparatively different residential proposals of collective dwellings as a function of density. The objective of the work is to evaluate, from an architectural design dimension, significant cases of collective housing built in Córdoba city that offer higher levels of densification in relation to the building environment where they are located. It seeks to identify the advantages in terms of residential quality in the different housing proposals that integrate the cases of study and link it with the density adopted in its design. The methodological approach integrates an evaluation matrix that compares housing complexes with different density values. Analytical dimensions related to urban indicators are selected and others with indicators relating to the design of collective housing.Weighting criteria are used to construct a residential quality index (RQI), andto integrate in a simulation model of the concepts: Density and Residentialquality. Finally, the results obtained in this first analytical approach of theproblem of study are evaluated new interrogations proposed to advance in theanalysis of the different levels of densification that are presented in the proposals and their adequacy.